2005
DOI: 10.1152/ajpgi.00346.2004
|View full text |Cite
|
Sign up to set email alerts
|

Luminal adenosine stimulates chloride secretion through A1receptor in mouse jejunum

Abstract: sine is known to stimulate chloride secretion by mouse jejunum. Whereas the receptor on the basolateral side is believed to be A2B, the receptor involved in the luminal effect of adenosine has not been identified. We found that jejuna expressed mRNA for all adenosine receptor subtypes. In this study, we investigated the stimulation of chloride secretion by adenosine in jejuna derived from mice lacking the adenosine receptors of A1 (A1R) and A2A (A2AR) or control littermates. The jejunal epithelium was mounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The earliest descriptions of the prosecretory effect of ADO in intestine were reported in 1984, in which basolateral addition of ϳ0.5 to 1.0 mM ADO to chambered rabbit ileum or colon in vitro elicited an increase in electrogenic net Cl Ϫ secretion (Dobbins et al, 1984;Grasl and Turnheim, 1984). More recently, numerous groups have reported the prosecretory effects of ADO in cultured epithelial cells or mounted intestinal tissues through the activation of A 2 or A 1 receptors, respectively (Ghanem et al, 2005;Novak et al, 2008;Wang et al, 2008;Rajagopal and Pao, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest descriptions of the prosecretory effect of ADO in intestine were reported in 1984, in which basolateral addition of ϳ0.5 to 1.0 mM ADO to chambered rabbit ileum or colon in vitro elicited an increase in electrogenic net Cl Ϫ secretion (Dobbins et al, 1984;Grasl and Turnheim, 1984). More recently, numerous groups have reported the prosecretory effects of ADO in cultured epithelial cells or mounted intestinal tissues through the activation of A 2 or A 1 receptors, respectively (Ghanem et al, 2005;Novak et al, 2008;Wang et al, 2008;Rajagopal and Pao, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research regarding extracellular ADO signaling in the gut has addressed enteric neurons, smooth muscle, afferent neurons, and the immune system, with relatively few studies addressing its effect on epithelial secretory function. Of these, even fewer have reported the effect of luminal ADO on ion secretion in intact epithelia in vivo, because most published studies reported short-circuit current (I sc ) measured in intestinal T84 monolayers (Barrett et al, 1989;Strohmeier et al, 1995) or mounted mammalian intestinal tissues (Dobbins et al, 1984;Grasl and Turnheim, 1984;Ghanem et al, 2005). Because apical or basolateral ADO stimulated I sc , ADO receptors were predicted to be expressed on both epithelial surfaces (Barrett et al, 1989;Strohmeier et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the airway epithelia, it seems that A 2B receptors regulate Cl − secretion and A 2A/B receptors regulate Na + absorption [3,7,15]. In the small intestine, luminal A 1 receptors stimulate Cl − secretion [12], and in the colon, the A 2B receptors are expressed on the luminal and basolateral membrane and stimulate Cl − secretion [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effect on immune cell migration and function, A1 receptor has been shown to play a significant role in luminal adenosine-induced chloride secretion in human jejunum (54). In a study using rigorous electrophysiological techniques, the investigators demonstrated that luminal adenosine-induced chloride secretion was mediated by A1 receptor even though A2b receptor was the most abundant adenosine receptor expressed in jejunal mucosa.…”
Section: A1 Receptormentioning
confidence: 99%
“…Esophagus, stomach, duodenum, jejunum, colon, cecum (124) (54,84), involved in enteric neuronal function (10) ?…”
Section: P2x Receptorsmentioning
confidence: 99%